1992
DOI: 10.1095/biolreprod46.6.1047
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Sperm Viability with Gamete Interaction and Fertilization in Vitro in the Cheetah (Acinonyx Jubatus)1

Abstract: Sperm-oocyte interaction in vitro was studied in the cheetah, a species known to produce poor quality ejaculates and to experience low rates of fertility. Twelve female cheetahs were injected (i.m.) with eCG followed by hCG 84 h later. Twenty-four to 26 h post hCG, each was subjected to laparoscopic oocyte aspiration. A sperm motility index (SMI) was calculated for each of 9 cheetah sperm donors that produced ejaculates averaging 41.3 +/- 22.9 x 10(6) motile sperm and 28.4 +/- 4.9% structurally normal sperm. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 14 publications
3
44
1
Order By: Relevance
“…Fortunately, there are excellent baseline data available from years of study into the reproductive biology of the domestic cat (Wildt 1991a). Success with assisted reproduction in the domestic cat (Goodrowe et al 1988, Howard et al 1992) also provides model data which can potentially short-cut similar experimentation in other species (Wildt et al 1986b). However, some reproductive parameters can differ quite sharply even between closely related species , Brown et al 1993, but with captive breeding programs as the catalyst, a substantial database is gradually being built up about the reproductive biology of different species (Wildt 1992b, Wildt et al 1993a.…”
Section: Advances In Assisted Reproductionmentioning
confidence: 99%
“…Fortunately, there are excellent baseline data available from years of study into the reproductive biology of the domestic cat (Wildt 1991a). Success with assisted reproduction in the domestic cat (Goodrowe et al 1988, Howard et al 1992) also provides model data which can potentially short-cut similar experimentation in other species (Wildt et al 1986b). However, some reproductive parameters can differ quite sharply even between closely related species , Brown et al 1993, but with captive breeding programs as the catalyst, a substantial database is gradually being built up about the reproductive biology of different species (Wildt 1992b, Wildt et al 1993a.…”
Section: Advances In Assisted Reproductionmentioning
confidence: 99%
“…The number of pronuclei and extrusion of the second polar body are used to ascertain the ploidy of fertilized oocytes in vitro (Braude 1987, Vanderhyden & Armstrong 1989, Donoghue et al 1992. The refractile structures observed in all oocytes that cleaved were assumed to be pronuclei.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that IVF and subsequent embryo culture rates did not differ between the fresh and thawed sperm treatments suggested that tiger spermatozoa were relatively unaffected by this cryopreservation approach. We have speculated (Donoghue et al, 1990) that one reason that tiger spermatozoa interact so readily with eggs in vitro is related to their robustness and the lack of structural abnormalities commonly observed in other felid species (Wildt et ai, 1983(Wildt et ai, , 1988Howard et al, 1984;Miller étal., 1989;Donoghue et al, 1992). In nonfelid taxa, cryopreservation can cause extensive gross and ultrastructural sperm damage that can markedly compromise fertility (Pursel et ai, 1972;Berndston et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Tiger embryos generated by IVF have also resulted in live young (Donoghue et al, 1990). The high efficiency of IVF in tigers, compared with that in other wild felids (Goodrowe et ai, 1989;Miller et al, 1989;Donoghue et al, 1992), appears to be related to the ability of tigers to ejaculate semen containing high proportions of structurally normal spermatozoa of high motility (Donoghue et al, 1990;Wildt et ai, 1992).…”
Section: Introductionmentioning
confidence: 99%